Wybrane problemy implementacji koncepcji zintegrowanej rachunkowości - Kucharska, Natalia; Kucharski, Adam (Integrated Accounting Concept Implementation Problems, 2007)
This article presents new concept named "integrated accounting" which merges financial, managerial and tax accounting in one information system. The implementation of integrated accounting concepts in F.RP systems is based on the results of special form of analysis which provides complex evidence for each business transaction in three-dimensonial accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 322-331